Secrets and Truths : Ethnography in the Archive of Romania's Secret Police - Verdery, Katherine, 1948- (Book collections on Project MUSE., 2014)
Nothing in Soviet-style communism was as shrouded in mystery as its secret police. Its paid employees were known to few and their actual numbers remain uncertain. Its informers and collaborators operated clandestinely under pseudonyms and met their officers in secret locations. Its files were inaccessible, even to most party members. The people the secret police recruited or interrogated were threatened so effectively that some never told even their spouses, and many have held their tongues to this day, long after the regimes fell. With the end of communism, many of the newly established governments--among them Romania's--opened their secret police archives. From those files, as well as her personal memories, the author has carried out historical ethnography of the Romanian Securitate. Secrets and Truths is not only of historical interest but has implications for understanding the rapidly developing "security state" of the neoliberal present